A descriptive survey on the role of Pinterest in the schematic design phase of interior design projects of selected licensed interior designers in Metro Manila - Bautista, Marie Paige Seven L.
The study examined the role of Pinterest in the schematic design phase of interior design projects based on the experience of selected licensed interior designers. The interview respondents were selected through purposive sampling based on set criteria. Eight 8 licensed interior designers from Metro Manila who mostly handled residential design projects participated in this study. Their years of experience as licensed interior designers ranged from 1 year to 10 years. A descriptive survey approach was used in which both quantitative and qualitative data were gathered through open ended interviews as well as a visual content analysis of schematic boards and photographs. Data findings were analysed into thematic tables through a grounded theory approach. The findings of the study show that Pinterest is encountered in practice mostly through clients who bring their own images to the designer. Ethical issues are being faced by interior designers when clients insist on wanting to copy a specific existing design. Visual content analysis done on submitted materials show how designers may tend to copy design inspirations found on Pinterest. 6 of 8 respondents acknowledge this as an ethical concern, and discussed several methods of avoiding this to happen. In completing the designers tasks and objectives in the schematic design phase, Pinterest mostly works as a wide database of images and has proven to be an efficient method for designers to align with the client s vision. Aside from assisting in designer client communication, Pinterest also became an aid in speeding up design team collaboration by providing a venue for designers to work together online.